Retroanálise de ruptura de estrutura de contenção em retangulões em Belo Horizonte/MG - Sandro Eduardo Lima Pinto (2013)
This work is presented a real case of a rupture of the retaining wall in rectangular dig technique, alternative stabilization commonly practiced in Belo Horizonte / MG. The event occurred in 2003 and was back-analyzed by geotechnical devices and computational tools available today, in order to understand and the record of what happened to other professionals, the causes that came collapse of such a structure. It described the technique executive of rectangular digs solution to perform regional executive contentions in places with irregular topography and difficult access equipment. We analyzed field tests and laboratory tests in order to evaluate the design parameters used, employing the results of these studies in computer simulations that could indicate the strengthparameters at the time of the collapse. Finally, after back-analysis of structural elements at moment of the break, as well as numerical simulations of equilibrium limit and stress-strain, it was possibleto play the hypothetical scenario geotechnical - climate which was responsible for failure of the containment structure.